The Effects Of Family Support, Social Support, And The Role Of Health Workers On The Reproductive Health Behavior Of Blind Adolescents In Sukabumi City And Regency - Haryani, Hana; Said, Faridah Mohd; Umar, Nur Syazana (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2025)
Adolescents with disabilities or special needs are very vulnerable to various health problems including reproductive health. In helping to maintain reproductive health, of course, there needs to be other factors that can support the achievement of reproductive health maintenance such as family support, social support and the role of health workers. The purpose of this study is to determine the influence of family support, social support and the role of health workers on the reproductive health of blind adolescents in the Sukabumi City Area and Sukabumi Regency. This type of research is correlational with the cross sectional approach. The population and s ampel as many as 42 adolescents with visual disabilities in sukabumi city and sukabumi regency used total sampling. Statistical analysis uses multiple linear regression. The results showed that there was a significant influence of information sources on the reproductive health behavior of adolescents with visual disabilities (p-value 0.000), there was a relationship of knowledge on the reproductive health behavior of adolescents with visual disabilities (p-value 0.000), and there is knowledge of attitudes towards reproductive health behaviors of adolescents with visual disabilities (p-value 0.000). and there is a simultaneous influence of sources of information, knowledge and attitudes towards reproductive health behaviors of adolescents with visual disabilities (p-value 0.000). It can be concluded that sources of information, knowledge and attitudes have an influence on the reproductive health behavior of adolescents with visual disabilities. The findings in this study can be used as a reference for relevant agencies and the government regarding the protection of adolescents with visual disabilities